Discrimination and authentication of lard blending with palm oil in cosmetic soap formulations - Ab Aziz, Atiqah; Abdullah Sani, Muhamad Shirwan; Zakaria, Zalina; Abu Bakar, Nor Kartini (Society of Cosmetic Scientists and Societe Francaise de Cosmetologie, 2023)
Background: The employment of Fourier transforms infrared (FT-IR) spectroscopy combined with chemometrics for determination and quantification of lard in a binary blend with palm oil in a cosmetic soap formulations. Objective: To determine and quantify lard as an adulterant in a binary blend with palm oil in a cosmetic soap formulations by FT-IR and multivariate analysis. Methods: Fatty acids in lard, palm oil and binary blends were extracted via liquid–liquid extraction and were subjected to FTIR spectrometry, combined with principal component analysis (PCA) and discriminant analysis (DA) for the classification of lard in cosmetic soap formulations via two DA models: Model A (percentage of lard in cosmetic soap) and Model B (porcine and non-porcine cosmetic soap). Linear regression (MLR), partial least square regression (PLS-R) and principal components regression (PCR) were used to assess the degree of adulteration of lard in the cosmetic soap. Findings: The FTIR spectrum of palm oil slightly differed from that of lard at the wavenumber range of 1453 cm−1 and 1415 cm−1 in palm oil and lard, respectively, indicating the bending vibrations of CH2 and CH3 aliphatic groups and OH carboxyl group respectively. Both of the DA models could accurately classify 100% of cosmetic soap formulations. Nevertheless, less than 100% of verification value was obtained when it was further used to predict the unknown cosmetic soap sample suspected of containing lard or a different percentage of lard. The PCA for Model A and Model B explained a similar cumulative variability (CV) of 92.86% for the whole dataset. MLR and PCR showed the highest determination coefficient (R2) of 0.996, and the lowest relative standard error (RSE) and mean square error (MSE), indicating that both regression models were effective in quantifying the lard adulterant in cosmetic soap. Conclusion: FTIR spectroscopy coupled with chemometrics with DA, PCA and MLR or PCR can be used to analyse the presence of lard and quantify its percentage in cosmetic soap formulations